Resistance to thyroid hormone beta coexisting with papillary thyroid carcinoma—two case reports of a thyroid hormone receptor beta gene mutation and a literature review - Fang, Yingxin; Liu, Tingting; Hou, Huimin; Wang, Zhihong; Shan, Zhongyan; Cao, Yanli; Teng, Xiaochun (Frontiers in Genetics, 2022)
Abstract Resistance to thyroid hormone (RTHβ) is an autosomal dominant hereditary disorder that is difficult to diagnose because of its rarity and variable clinical features, which are caused by mutations in the thyroid hormone receptor beta (THRB) gene. Recent studies have indicated a close association of THRB mutations with human cancers, but the mechanism of THRB mutation in carcinogenesis is unknown. Herein, we report two cases of RTHβ coexisting with papillary thyroid carcinoma (PTC) and their follow-up results. Two female patients presented with elevated serum thyroid hormone levels and nonsuppressed thyrotropin (TSH). Genetic analysis showed that each patient had a THRB gene mutation (p.P453T and p.R320H). Based on the results of ultrasound-guided fine-needle aspiration biopsy, the thyroid nodules were suspected to be PTC. Intraoperative pathology confirmed that the two patients had PTC with multifocal carcinoma of both lobes. One patient underwent a total thyroidectomy and central lymph node dissection, and the other underwent a total thyroidectomy. Following surgery, large doses of levothyroxine were administered to suppress TSH levels to prevent recurrent or persistent disease. However, it is difficult to continually suppress TSH levels below the upper limit of the normal range. To date, the two patients have no recurrence of PTC on ultrasound.